The Impact of Online Reviews on the Information Flows and Outcomes of Marketing Systems. (March 2022) - Watson, Forrest; Wu, Yinglu
Online reviews are changing the way that consumers shop and firms respond to consumer feedback. Viewed more broadly, online reviews are a type of information flow altering the functioning of marketing systems at the micro, meso, and macro levels. A systematic review of the past two decades of research shows great attention to the impact of online reviews on information flows, as well as the nuances of micro-and meso-level efficiency outcomes. However, there is scant consideration for the effectiveness related outcomes of online reviews (such as customer well-being, distributive justice, and externalities). Through a macromarketing lens, online reviews are an information flow with the potential to change well-being outcomes for all stakeholders, rather than just a tool to be exploited by firms or consumers. A theoretical framework and a series of questions are presented for future research on how online reviews and more generally information flows between actors may impact the efficiency and effectiveness of a marketing system.